2020
DOI: 10.1002/pd.5684
|View full text |Cite
|
Sign up to set email alerts
|

Maternal thyroid disease and its effects on the fetus and perinatal outcomes

Abstract: Thyroid disease is common in women of childbearing age and can have significant effects on the development of the fetus and perinatal outcomes. Maternal thyroid hormone is critical for proper fetal neurodevelopment, and the fetus relies on thyroid hormone from its mother for the first half of pregnancy. Both overt maternal hypothyroidism and overt maternal hyperthyroidism have been shown to be associated with adverse effects on central nervous system gray matter and neurocognitive development of offspring as w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 99 publications
(296 reference statements)
1
12
0
Order By: Relevance
“…Maternal hormones are suggested to cause long-lasting effects on offspring via changes in the function and sensitivity of the corresponding hormonal axis 3 , so-called organizational effects. Changes in hypothalamus–pituitary–thyroid (HPT)-axis in response to prenatal THs during embryonic development has been characterized in chicken 50 , pigeons 18 as well as mammalian models (reviewed in 51 ). Our results suggest an absence of such long-term programming effects of the HPT-axis in our study system—however it must be noted that circulating TH levels are highly variable in response to internal and external (food, temperature, circadian) variations 4 , 49 , which could mask potential organizing effects.…”
Section: Resultsmentioning
confidence: 99%
“…Maternal hormones are suggested to cause long-lasting effects on offspring via changes in the function and sensitivity of the corresponding hormonal axis 3 , so-called organizational effects. Changes in hypothalamus–pituitary–thyroid (HPT)-axis in response to prenatal THs during embryonic development has been characterized in chicken 50 , pigeons 18 as well as mammalian models (reviewed in 51 ). Our results suggest an absence of such long-term programming effects of the HPT-axis in our study system—however it must be noted that circulating TH levels are highly variable in response to internal and external (food, temperature, circadian) variations 4 , 49 , which could mask potential organizing effects.…”
Section: Resultsmentioning
confidence: 99%
“…It ranges from asymptomatic carriers to patients with primary APS, defined according to the classification criteria [24], and includes patients with aPL who present obstetric manifestations not included in these criteria but represent a very relevant subgroup in routine clinical practice. Another advantage of our study is that in addition to the cardiovascular risk factors and the serological profile, we have also included other comorbidities that could influence the overall obstetric prognosis [51][52][53][54]. Although we did not find significant differences in these comorbidities when we analyzed the groups of aPL carriers, after stratifying by aGAPSS, the patients included in the low-risk group did present a higher proportion of obstetric comorbidities (p = 0.027 compared with the medium risk and p = 0.11 with high-the risk group).…”
Section: Discussionmentioning
confidence: 99%
“…Any abnormality in maternal thyroid levels during pregnancy hampers fetal growth since thyroid hormones are critical for the normal growth and development of the human fetus [15]. Thus, maintaining an optimum concentration of thyroid hormones is a requisite for ensuring a healthy pregnancy as aberrant changes in thyroid levels negatively affects the fetal development particularly the development of the central nervous system and neurocognitive development of offspring as well [16]. Several studies have indicated that both hypothyroidism and hyperthyroidism have been associated with abortions, stillbirths, preterm delivery, LBW, and pregnancy-induced hypertension thereby increasing incidences of neonatal morbidity and mortality [17][18][19].…”
Section: Discussionmentioning
confidence: 99%